2022
DOI: 10.1099/mgen.0.000867
|View full text |Cite
|
Sign up to set email alerts
|

A general approach to identify low-frequency variants within influenza samples collected during routine surveillance

Abstract: Influenza viruses exhibit considerable diversity between hosts. Additionally, different quasispecies can be found within the same host. High-throughput sequencing technologies can be used to sequence a patient-derived virus population at sufficient depths to identify low-frequency variants (LFV) present in a quasispecies, but many challenges remain for reliable LFV detection because of experimental errors introduced during sample preparation and sequencing. High genomic copy numbers and extensive sequencing de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…In support of this suggestion, prior work on respiratory syncytial virus sequencing found that, below allele frequencies of 25%, variant calling across a range of coverages, variant callers, and a range of simulated error profiles resulted in a precision of less than 50%, approaching 0% at allele frequencies below 5% [ 30 ]. Additionally, sequencing analysis on influenza samples has found that minor alleles cannot be confidently called at frequencies below 5% [ 31 ], and that without correction to the methods, minor variants were overestimated by as much as 10-fold [ 32 ]. These studies also identified several methods to improve confidence in variant calls, including generating technical replicates for each sample and adjusting allele-frequency thresholds based on Polymerase Chain Reaction (PCR) cycle threshold values, both of which underscore the need for rich metadata to support thorough and accurate use of public sequence data and the need to consider consensus sequences carefully in the absence of such metadata.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this suggestion, prior work on respiratory syncytial virus sequencing found that, below allele frequencies of 25%, variant calling across a range of coverages, variant callers, and a range of simulated error profiles resulted in a precision of less than 50%, approaching 0% at allele frequencies below 5% [ 30 ]. Additionally, sequencing analysis on influenza samples has found that minor alleles cannot be confidently called at frequencies below 5% [ 31 ], and that without correction to the methods, minor variants were overestimated by as much as 10-fold [ 32 ]. These studies also identified several methods to improve confidence in variant calls, including generating technical replicates for each sample and adjusting allele-frequency thresholds based on Polymerase Chain Reaction (PCR) cycle threshold values, both of which underscore the need for rich metadata to support thorough and accurate use of public sequence data and the need to consider consensus sequences carefully in the absence of such metadata.…”
Section: Discussionmentioning
confidence: 99%